Limestone Calcined Clay Cement as A Green Construction Material - Smita Sambhaji Patil; Vaishnavi Shailesh Jadhav; Shreya Satish Nalavade; Mayur Madhukar Maske (Universitas Pendidikan Indonesia (UPI), 2022)
Supplementary Cementitious Materials (SCMs) are promising components as substitutes for clinker components in cement and at the same time become a solution in reducing CO2 emissions and increasing sustainable development. The main objective of this study is to focus on production, techno-economic feasibility, and environmental impact, and cost-effectiveness of the limestone calcined clay cement (LC3). LC3 is a new type of cement-based on a blend of limestone and calcined clay. A combination of calcined clay with limestone allows higher levels of substitution down to clinker contents of around 50% with similar mechanical properties and improvement in some aspects of durability. The results showed that the feasibility of blending 50% of LC3 in cement. The hope is that these findings can help reduce carbon footprints in the construction industry.